1995
DOI: 10.1111/j.1536-7150.1995.tb03243.x
|View full text |Cite
|
Sign up to set email alerts
|

Alumni Donations and Colleges’Development Expenditures: Does Spending Matter?

Abstract: Since college development officers supply recognition to alumni and seek donations in return a model is devised wherein this exercise of market power in the exchange is included. Data for three years is used from eighteen universities and colleges-public and private, large and small, research and teachingoriented. The findings indicate that schools with higher development costs generate substantially more donations. Several demographic characteristics ofthe student body were tested. Schools with higher partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 13 publications
5
51
0
Order By: Relevance
“…Notably, the ' alumni -institutional relationship ' is a signifi cant discriminator to predict alumni giving ( Okunade et al , 1994 ;Harrison et al , 1995 ;Taylor and Martin, 1995 ;Hunter et al , 1999 ). Hunter et al 's (1999) study found alumni ' s motivation derived from emotional attachment to their alma-mater and their desire to give something back.…”
Section: Understanding Donor Motivationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the ' alumni -institutional relationship ' is a signifi cant discriminator to predict alumni giving ( Okunade et al , 1994 ;Harrison et al , 1995 ;Taylor and Martin, 1995 ;Hunter et al , 1999 ). Hunter et al 's (1999) study found alumni ' s motivation derived from emotional attachment to their alma-mater and their desire to give something back.…”
Section: Understanding Donor Motivationsmentioning
confidence: 99%
“…The fi ndings indicated that donor status had signifi cant correlation with independent variables such as ' family income, perceived need for fi nancial support, reading alumni publications, subsequent enrollment for graduate work, special-interest groups, and involvement with university as an alumnus / a ' ( Taylor and Martin, 1995, p. 299 ). Also, in the words of Harrison et al (1995) , ' donors seem to want the psychic satisfaction that accompanies recognition from their former schoolfrom appearing in a list of names in the alumni bulletin, to receiving free football tickets, to having a scholarship or building named after them ' (p. 398). Interestingly, proximity -domestic residence -was not a signifi cant predictor of alumni giving ( Hoyt, 2004 ).…”
Section: Understanding Donor Motivationsmentioning
confidence: 99%
“…For example, a number of studies link alumni giving to involvement in extracurricular activities while an undergraduate student (see Keller, 1982 ;Haddad, 1986 ;Harrison et al ., 1995 ;Dugan et al ., 2000 ;Monks, 2003 ).…”
Section: Social Exchange Theorymentioning
confidence: 99%
“…With the increasing competitiveness in the market, combined with rising educational costs and reductions in student fi nancial aid, college and university alumni are ever more essential in providing fi nancial support to their institutions ( Briechle, 2003 ;Liu, 2006 ;Weerts and Ronca, 2007 ). Research on giving to higher education generally has focused on predicting the factors and characteristics of alumni who give (e.g., Taylor and Martin, 1995 ;Baade and Sundberg, 1996 ;Okunade and Berl, 1997 ;Belfi eld and Beney, 2000 ;Clotfelter, 2003 ;Weerts and Ronca, 2007 ), the institutional and macroeconomic factors in explaining variations in giving (e.g., Briechle, 2003 ;Gunsalus, 2004 ;Liu, 2006 ), alumni motivation for giving (e.g., Diamond and Kashyap, 1997 ;Weerts and Ronca, 2007 ), fundraising practices in higher education (e.g., Harrison, 1995 ;Harrison et al , 1995 ), and the determinants of donor revenue (e.g., Cunningham and Cochi-Ficano, 2001 ; see review of literature in Liu, 2006 ).…”
Section: Purpose Of the Studymentioning
confidence: 99%